Pemanfaatan Ragi Tapai dan Getah Buah Pepaya pada Ekstraksi Minyak Kelapa secara Fermentasi - Cut Erika; Yunita Yunita; Normalina Arpi (Agricultural Faculty, 2014)
(The Use of Tapai Yeast and Papaya Fruit Sap on Coconut Oil Extraction By Fermentation)ABSTRACT. In Aceh, coconut oil extraction is traditionally done through a natural fermentation of fresh coconut meat to produce simplah and pliuk u oil. Simplah oil and pliek u oil have high level of moisture content, free fatty acids, and peroxide value due to long fermentation process. The study was conducted by using the fresh shredded coconut meat. Then mixed with tapai yeast and papain from immature papaya fruit sap and were fermented for 48, 72, and 96 hours respectively. The yield of coconut oil produced in this study was from 8.53 % - 19.0 %, moisture content 12.58 - 2.66 %, free fatty acid content 3.29 % - 11:55 %, and peroxide value 0.76 - 1.75 mg O2/g of oil sample. The highest yield of coconut oil was obtained in the control treatment which significantly different from other treatments. The highest moisture content and free fatty acid were obtained on the treatment of using tapai yeast during fermentation process of coconut oil and did not meet the requirements set by the Indonesian National Standard (SNI 01-2902-1982), while the peroxide value of coconut oil produced in various treatment have met the criteria of SNI. The average organoleptic score of coconut oil color 3.38 (from moderate to clear) which the highest score was obtained on fermented coconut oil with the addition of tapai yeast. The highest hedonic score of aroma was found in the coconut oil fermented with the addition of papain from papaya fruit sap with fermentation time of 48 hours is 2.9 (from dislike to moderate).